Effects of Epichloë gansuensis Endophyte on the Root and Rhizosphere Soil Bacteria of Achnatherum inebrians Under Different Moisture Conditions - Ju, Yawen; Zhong, Rui; Christensen, Michael J.; Zhang, Xingxu (Frontiers in Microbiology, 2020)
This study was conducted to explore effects of the presence of the systemic fungal endophyte Epichloë gansusensis on root and rhizosphere soil bacteria diversity of Achnatherum inebrians host plants growing under different soil moistures, through the pyrosequence technology targeting the bacteria 16S rRNA gene, and soil properties of different treatments were compared using standard techniques. A total of 4371379 16S rRNA gene sequences were obtained and assigned to 5025 operational taxonomic units (OTUs). These OTUs in roots and rhizosphere soil were divided into 13 and 17 phyla respectively, and the Actinobacteria and Proteobacteria were the most abundant phyla both in roots and rhizosphere soil. Additionally, our results indicated that E. gansusensis, soil moisture, and their interactions significantly affected root and rhizosphere soil bacteria community diversity. Shannon diversity and Chao1 richness index of bacteria in rhizosphere soil was significantly higher than in roots. Structural equation modeling also emphasized that E. gansusensis and soil moisture increased the diversity of the root-associated bacteria community, and soil moisture decreased the diversity of the rhizosphere soil bacteria community. The E. gansusensis endophyte and soil moisture effects on root and rhizosphere soil bacteria diversity were likely to be from responses to modifications of the rhizosphere soil properties.